Analyzing Iago's Speech in Shakespeare's Othello - Nimer Abuzahra; Rami Salahat (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
This paper aims to reveal and analyze Iago's speech in Shakespeare's Othello. Iago's use of animal metaphors in Othello is analyzed through Conceptual Metaphor Theory (CMT). Moreover, Iago's words in the play are connected to race, gender and identity and analyzed through Critical Discourse Analysis (CDA). Finally, Iago's rhetorical discourse is analyzed through Rhetorical Theory to examine his use of rhetorical devices such as rhetorical questions. The findings of this study show that Iago's use of animal metaphors in the play is to dehumanize and degrade other characters. Further, Iago is able to alienate Othello because of his different identity and different color from the Venetian society. What's more, Iago has shown misogynistic attitudes toward women through the course of the play. In addition, Iago shows an exceptional ability in his rhetoric. He manipulates most of the characters in the play and was able to deceive all of them. It can be concluded, then, that Iago's use of animal metaphors is conceptualized and connected to his cognitive mind. Moreover, Iago's racist language in the play reflects the racist attitudes toward 'non-white' people in Shakespeare's time. Finally, Iago uses different rhetorical techniques such as rhetorical questions to manipulate other characters which shows how language can be exploited to achieve negative impact on others.